A personal perspective on mathematical economics - GOODWIN, R. (PSL Quarterly Review, 2013)
The paper is a contribution to a series of recollections and reflections on the professional experiences of distinguished economists which the Banca Nazionale del Lavoro Quarterly Review started in 1979. In it Richard Goodwin offers a retrospective on his intellectual development. JEL: B31, C00